The Soul of Black Preaching - Croft, Wayne E. (Theology today, 2024)
This article explores the richness of African American preaching. It contends that preaching is central in African American worship and interweaves aspects of African traditional religion. It reviews certain theological and rhetorical characteristics of Black preaching, such as poetic storytelling, call and response, rhythm, and musical sound. This article further contends that the soul of Black preaching is both an art and a discipline. It is also a historical, life-giving, and empowering entity, reflecting a rich tapestry of culture, communication, inspiration, faith, and empowerment within the African American religious tradition.